Agronomic Effectiveness of Calcined Phosphate (Phospal-34) on Maize (Zea mays L.) - Piya Duangpatra; Paiboon Prabuddham; Chairerk Suwannarat (Agriculture and Natural Resources, 1993)
Afield experiment was conducted to evaluate the relative effectiveness of calcined phosphate, Phospal-34 (PP-34), on growth and yield of corn. Fertilizer treatments assessed comprised application of P fertilizers from various combination of Diammonium phosphate (DAP) and PP-34. Corn was grown on a loamy soil and the weights of dry stover, grain yield and P concentrations in plant were measured. Corn grown on loamy soil showed substantial responses to N, P and K fertilizers. Mixed fertilizers containing PP-34 and DAP as P materials at various proportions were as effective as PP-34-free mixed fertilizers. Moreover, mixed fertilizers containing P from both PP-34 and DAP tended to be superior to mixed fertilizers containing P solely from PP-34. Based on the results of this experiment, it was apparent that mixed fertilizer containing 44% and 56% of total available P derived from PP-34 and DAP, respectively was the best formulation for maize.